Seed Invigoration with Antioxidants Improves Growth and Yield Attributing Characters in Soybean - UMESH KAMBLE; MT BHINGARDE; VIJAY SHELAR; RM NAIK; MP DESHMUKH (Seed Research, 2026)
A field experiment was conducted on four soybean (Glycine max L.) cultivars viz., JS-335, DS-228, KDS-726 and Type-49 to study the effect of seed invigoration with varied antioxidants (Ascorbic acid, α-tocopherol and Butylated Hydroxytoluene) on growth and yield attributing characters during kharif 2016 and kharif 2017 at Post Graduate Institute Research Farm, Department of Agricultural Botany, Mahatma Phule Krishi Vidyapeeth, Rahuri. Field observations such as field emergence percentage, days to 50 % flowering, plant height, number of primary branches per plant, number of pods per plant, days to maturity, seed yield per hectare and seed index were recorded. Among the seed invigoration treatments, seed invigorated with α-tocopherol (200 ppm) exhibited higher field emergence percentage, plant height, number of pods per plant, seed yield per plant, seed yield per hectare and seed index. The seeds of variety KDS-726 invigorated with α- tocopherol (200 ppm) followed byascorbic acid (100 ppm) were found effective in increasing seed yield due to increase in field emergence, number of pods per plant, number of primary branches, seed index and seed yield per plant and seed yield per ha than varieties viz., DS-228, JS-335 and Type-49.